Study on effect of insulation of wall to the building energy efficiency in hot and humid climate - Hanafiyah, Bin Othman (Universiti Malaysia Sarawak, UNIMAS, 2010)
This work was initiated to investigate the effect of insulation of wall to the building energy efficiency in hot and humid climate. According to Malaysia Energy Centre (2009), buildings are recognized as the second largest consumer of energy. The objective of this project is to study the effect of wall insulation on building envelope or thermal behavior in buildings. Experiments will be conducted and validated for a dynamic thermal model computer simulation. The simulated results later will determine the significances of utilizing the insulation in the wall. This project would help Malaysian buildings to reduce and conserve energy for human comfort. Energy efficiency is important as it contributes a cleaner environment and preserves the ecological system on earth.